Modelling length of hospital stay in motor victims - Mercedes Ayuso-Gutiérrez; Lluís Bermúdez-Morata; Miguel Santolino-Prieto (Instituto Nacional de Salud Pública, 2015)
Objective. To analyze which socio-demographic and other factors related to motor injuries affect the length of hospital recovery stay. Materials and methods. In the study a sample of 17 932 motor accidents was used. All the crashes occurred in Spain between 2000 and 2007. Different regression models were fitted to data to identify and measure the impact of a set of explanatory regressors. Results. Time of hospital stay for men is on average 41% larger than for women. When the victim has a fracture as a consequence of the accident, the mean time of hospital stay is multiplied by five. Injuries located in lower extremities, the head and abdomen are associated with greater hospitalization lengths. Conclusions. Gender, age and type of victim, as well as the location and nature of injuries, are found to be factors that have significant impact on the expected length of hospital stay.